An Experimental Study on the Effect of Thermally Oxidised Ti-6Al-4V Substrate on the Surface Characteristics and Composition of Hydroxyapatite Coatings Produced by Modified Cold Gas Spray - Norarney Ahmad; Norehan Mokhtar; Siti Noor Fazliah Mohd Noor; Hussain Zuhailawati; Suzianti Iskandar Vijaya (Journal of Clinical and Diagnostic Research, 2025)
Introduction: Hydroxyapatite (HA) coatings enhance the bioactivity of Titanium-6% Aluminum-4% Vanadium (Ti-6Al-4VTi-6Al-4V). Conventional plasma spraying often results in amorphous HA phases due to high temperatures. To overcome this, HA coatings can be deposited at lower temperatures using a modified Cold Gas Spray (CGS) technique. The present study compared the effects of thermally oxidised and sand-gritted substrates on the properties of HA coatings. Aim: To evaluate the impact of thermal oxidation on surface topography, roughness, thickness, phase composition and the Calcium-to-phosphorus (Ca/P) molar ratio of HA coatings applied via modified CGS. Materials and Methods: An experimental study was conducted at the School of Material and Mineral Resources Engineering, Engineering Campus, Universiti Sains Malaysia (USM), Malaysia, from May 2021 to May 2023. Ti-6Al-4V substrates were sand-gritted and thermally oxidised at temperatures ranging from 450°C to 600°C. HA coatings were applied using the modified CGS. Coatings were analysed using Atomic Force Microscopy (AFM), Backscattered Electron Microscopy (BSEM), X-Ray Diffraction (XRD) and X-ray Fluorescence (XRF) to investigate surface roughness, surface topography, coating thickness and composition. Statistical analysis was performed using the Kruskal-Wallis test for group comparisons, followed by post-hoc Mann-Whitney U tests. A p-value of less than 0.05 was considered statistically significant. Results: Thermally oxidised substrates exhibited increased surface roughness and microhardness compared to the sand-gritted control. The HA coating on sand-gritted substrates had a roughness of 60.43 nm (IQR=37.41 nm), while oxidised surfaces at 500°C and 600°C resulted in roughness values of 27.61 nm (IQR=51.07 nm) and 33.03 nm (IQR=23.19 nm), respectively. A 2D image showed no aggregation of HA particles. Coating thickness was reduced from 109.0 μm (IQR=45.3 μm) on sand-gritted substrates to 48.4 μm (IQR=12.5 μm) on substrates oxidised at 600°C. The thermally oxidised substrate at 500°C produced a coating thickness of 74.2 μm (IQR=9.40 μm) with a Ca/P ratio of 1.83, meeting the Food and Drug Administration (FDA) standard. XRD confirmed that the phase composition of all coatings was consistent with the original HA powder. Conclusion: Thermal oxidation of Ti-6Al-4V substrates influences the roughness and thickness of HA coatings’ surfaces and the modified CGS technique produces HA coatings suitable for biomedical applications.